2017
DOI: 10.1016/j.matdes.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of electrospun poly(ethylene oxide) ultra-fine fibres with incorporated MoO3 nanoparticles

Abstract: N-type semiconducting molybdenum trioxide (MoO3) nanoparticles embedded in polyethylene oxide (PEO) polymer ultra-fine fibres were deposited directly onto silicon substrates using an electrospinning technique. The effects of different MoO3/PEO concentrations as well as electrospinning parameters on the fibre morphologies were examined. Experimental results show that embedding nanoparticles and electrospinning onto small areas can be achieved without use of solvents or transfer of the deposited nanostructures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…During the evolution of the electrospinning technique to modern times, Reneker and co-workers [ 49 50 ] have made a remarkable contribution by producing a diverse range of electrospun NFs of various morphologies, sizes and for various applications [ 51 55 ]. More recently, Deitzel et al [ 56 ] and Shafiei et al [ 57 ] developed a method to dampen the chaotic motion of the charged jet using electrostatic rings with a better control of the deposition area that is crucial for depositing 1D nanostructures on miniature sensing platforms (i.e., micro-electromechanical systems (MEMs)).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…During the evolution of the electrospinning technique to modern times, Reneker and co-workers [ 49 50 ] have made a remarkable contribution by producing a diverse range of electrospun NFs of various morphologies, sizes and for various applications [ 51 55 ]. More recently, Deitzel et al [ 56 ] and Shafiei et al [ 57 ] developed a method to dampen the chaotic motion of the charged jet using electrostatic rings with a better control of the deposition area that is crucial for depositing 1D nanostructures on miniature sensing platforms (i.e., micro-electromechanical systems (MEMs)).…”
Section: Reviewmentioning
confidence: 99%
“…Recently, Shafiei et al [ 57 ] reported electrospun ultrafine fibers with MoO 3 nanoparticles embedded in poly(ethylene oxide) (PEO) polymer by using the direct method. The fibers are deposited directly onto a controlled and selective deposition area using a multifield electrospinning setup as shown in Fig.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the spatial orientation of one-dimensional structures, nanoparticles can be uniformly dispersed along the axial direction of the nanomaterials, which can effectively be against the agglomeration of nanoparticles. Among the different strategies for producing one-dimensional metal oxide nanomaterials, electrospinning has proved a remarkably simple, straightforward and cost-effective process to obtain long continuous metal oxide nanofibers with a diameter ranging from submicrometre to nanometre scales [18][19][20][21][22]. To date, many groups have focused on designing one-dimensional transition-metal oxide nanofibers composed of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning has become a practical technique for production of nanofibers with diameters commonly ranging from tens to hundreds of nanometers because of its versatility and cost-effective setup [ 8 , 9 , 10 ]. These nanofibers usually have sufficient surface area and high porosity features, enabling them to be assembled and processed for a variety of applications [ 7 ], including biomimetic processes [ 11 ], sensors [ 10 , 12 ], and environmental fields [ 13 ].…”
Section: Introductionmentioning
confidence: 99%